APPLICATION OF ADMINISTRATIVE LAW AS PRIMUM REMEDIUM IN ERADICING CRIMINAL ACTS OF CORRUPTION - Maha, Rinto; Ginting, Budiman; Supandi, Supandi; Siregar, Mahmul (NOMOI Law Review, 2023)
Research on administrative law as the main instrument in eradicating criminal acts of corruption, because of several interesting things, including, the sanctions of imprisonment for special offenses of office crimes in the Dutch Criminal Code since it came into force on March 3 1881 where the law was initially lighter. In the course of more than a hundred years of its use in Indonesia, especially in office crimes (Tipikor), the criminal sanctions applied have become increasingly irrational. Historically, the use of the Dutch Criminal Code began to be applied to colonial territories, with several reconditions to colonial territories which had different sociological aspects, both Suriname and the Dutch East Indies . Hoekoeman Baroe Boewat Indies-Ollanda. This research is normative legal research or what is also known as library research and study of decision documents . The type of approach used in this research is a statutory approach ( statute approach ) carried out by examining all court decisions . The application of State administrative law as the Primum Remedium for eradicating corruption in Indonesia should be implemented in accordance with the spirit of the UNCAC Ratification (United Nations Convention). Against Corruption, 2003) Article 53 that Non-Conviction Based (NCB) Asset Confiscation or Action to return wealth directly can be carried out without punishment.